COMPARING NEGATIVE PRESSURE WOUND TREATMENT WITH HONEY DRESSING IN HEALING OF FOOT ULCERS IN DIABETICS: Honey Dressing in Healing of Foot Ulcers - Maqsood, Dr Rasikh; Bashir, Umar; Shabbir, Hassan (Pakistan Armed Forces Medical Journal, 2018)
Objective: To evaluate and compare the effectiveness of vacuum assisted treatment with that of honey dressing in duration of healing of foot ulcers in diabetics. Study Design: Randomized control study. Place and Duration of Study: Combined Military Hospital Multan & Nishtar Hospital Multan, from Aug 2016 till Feb 2017. Patients and Methods: A total of 95 patients with ages between 30-60 years of both sexes, who presented with diabetic ulcers of foot involving subcutaneous tissue& skin. Patients were divided randomly into two groups; Group V and H. Group V was subjected to Vacuum Pack closure (negative pressure wound treatment) and group H was treated with honey dressing, follow up was done till the appearance of healthy tissue after initial debridement, suitable for STSG (Split Thickness Skin Graft) or primary closure. Results: Healthy tissue appeared much faster in Vacuum assisted treatment, then with honey dressing with mean of 18.2 days for V.A.C and 28.8 days for honey dressing. Conclusion: Vacuum assisted closure was more effective in the treatment of foot ulcers in diabetics. It promotes healthy granulation tissue in the wound bed at a faster rate in comparison to honey dressing.